Photoprotection Mechanism of p‑Methoxy Methylcinnamate: A CASPT2 Study - Chang, Xue-Ping; Li, Chun-Xiang; Xie, Bin-Bin; Cui, Ganglong (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2015)
p-Methoxy methylcinnamate (p-MMC) shares the same molecular skeleton with octyl methoxycinnamate sunscreen. It is recently found that adding one water to p-MMC can significantly enhance the photoprotection efficiency. However, the physical origin is elusive. Herein we have employed multireference complete active space self-consistent field (CASSCF) and multistate complete active-space second-order perturbation (MS-CASPT2) methods to scrutinize the photophysical and photochemical mechanism of p-MMC and its one-water complex p-MMC–W. Specifically, we optimize the stationary-point structures on the 1ππ*, 1nπ*, and S0 potential energy surfaces to locate the 1ππ*/S0 and 1ππ*/1nπ* conical intersections and to map 1ππ* and 1nπ* excited-state relaxation paths. On the basis of the results, we find that, for the trans p-MMC, the major 1ππ* deactivation path is decaying to the dark 1nπ* state via the in-plane 1ππ*/1nπ* crossing point, which only need overcome a small barrier of 2.5 kcal/mol; the minor one is decaying to the S0 state via the 1ππ*/S0 conical intersection induced by out-of-plane photoisomerization. For the cis p-MMC, these two decay paths are comparable 1ππ* deactivation paths: one is decaying to the dark 1nπ* state via the 1ππ*/1nπ* crossing point, and the second is decaying to the ground state via the 1ππ*/S0 conical intersection. One-water hydration stabilizes the 1ππ* state and meanwhile destabilizes the 1nπ* state. As a consequence, the 1ππ* deactivation path to the dark 1nπ* state is heavily inhibited. The related barriers are increased to 5.8 and 3.3 kcal/mol for the trans and cis p-MMC–W, respectively. In comparison, the barriers associated with the photoisomerization-induced 1ππ* decay paths are reduced to 2.5 and 1.3 kcal/mol for the trans and cis p-MMC–W. Therefore, the 1ππ* decay paths to the S0 state are dominant relaxation channels when adding one water molecule. Finally, the present work contributes a lot of knowledge to understanding the photoprotection mechanism of methylcinnamate derivatives.